2015
DOI: 10.1590/1809-4430-eng.agric.v35n5p931-940/2015
|View full text |Cite
|
Sign up to set email alerts
|

Unidades combinadas RAFA-SAC para tratamento de água residuária de suinocultura – parte II nutrientes

Abstract: RESUMO:Neste trabalho, avaliou-se o efeito combinado de duas unidades de tratamento na remoção de nitrogênio total Kjeldahl (NTK) e fósforo total (PT). As unidades avaliadas receberam alimentação contínua, sendo um reator anaeróbio de manta de lodo e fluxo ascendente tipo RAFA, com volume útil de 96 L, seguido de um sistema alagado construído (SAC) As eficiências de remoção de NTK e PT no sistema como um todo foram de, aproximadamente, 35%, não havendo diferença significativa entre as fases. Porém, em termos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…However, Amorim et al (2015) observed nitrogen removal of the order of 30% (22.9 g d −1 ) in an upward flow anaerobic reactor when treating swine wastewater.…”
Section: Resultsmentioning
confidence: 98%
“…However, Amorim et al (2015) observed nitrogen removal of the order of 30% (22.9 g d −1 ) in an upward flow anaerobic reactor when treating swine wastewater.…”
Section: Resultsmentioning
confidence: 98%
“…Amorim et al (2015), mesmo trabalhando com taxas de carregamento de P superiores às avaliadas neste trabalhoentre 13 e 240 kg ha -1 d -1 -obtiveram baixa eficiência na remoção de P, que variou entre 20 e 30%. Lee et al (2004) também verificaram menores eficiências na remoção de P (47 a 59%) que as obtidas aqui.…”
Section: Remoção De Matéria Orgânicaunclassified
“…The different media and crop combination of the treatments did not interfere in the removal of Total-P. Mendonça et al (2012) verified that there was no significant difference between the cultivated and non-cultivated HSSF-CWs in the removal of phosphorus, with average efficiencies varying from 19 to 34%. Amorim et al (2015), worked with loading rates of P higher than those evaluated in this study, between 13 and 240 kg ha -1 d -1 , obtained efficiency in the removal of P, which varied between 20 and 30%.…”
mentioning
confidence: 54%